Systematic review and meta-analysis: real-world effectiveness of direct-acting antiviral therapies in chronic hepatitis C genotype 3 in Asia. Issue 1 (20th August 2018) - Wei, Bin; Ji, Fanpu; Yeo, Yee Hui; Ogawa, Eiichi; Stave, Christopher D; Dang, Shuangsuo; Li, Zongfang; Furusyo, Norihiro; Cheung, Ramsey C; Nguyen, Mindie H
Abstract : Background: Genotype 3 (GT3) is a common chronic hepatitis C (CHC) genotype in Asia. Direct-acting antiviral (DAA) regimens have high cure rates, but real-world results are limited for Asia. Aim: To determine the real-world effectiveness of DAAs for patients with CHC GT3 in Asia. Methods: A systematic search was performed in PubMed (including MEDLINE), Embase, and selected international meeting abstract repositories. Eligible studies were postmarketing observational studies from Asia with the primary outcome of sustained virological response 12 weeks after completion of treatment (SVR12). Results: A total of 15 studies with 4230 patients yielded a pooled SVR12 of 92.7%. High heterogeneity ( I 2 =93.2%, P <0.0001) was noted. In subgroup analyses, patients with cirrhosis had 10.9% lower SVR12 than non-cirrhotic patients (88.6% vs 98.9%; P <0.0001) and contributed 69.5% of the heterogeneity. Prior treatment failure did not reduce the pooled SVR12 (treatment-naïve: 94.6%, 95% CI 91.3% to 96.7% vs treatment-experienced: 94.0%, 95% CI 77.5% to 98.6%; P =0.89). Twenty-four weeks of sofosbuvir+ribavirin dual therapy was the most commonly used regimen which led to similar SVR12 (OR=1.1, P =0.73) but lower adverse event rate than 12 weeks of sofosbuvir+ribavirin+pegylated interferon triple therapy. Conclusion: Sofosbuvir+ribavirin for 24 weeks is the most widely used and generally well-tolerated DAA therapy in Asia. However, its effectiveness is not optimal in GT3 patients with cirrhosis.